Computational study of the vibrational spectroscopy properties of boron-hydrogen compounds: Mg(B3H8)2, CB9H10− and CB11H12−. (31st August 2017) - Sethio, Daniel; Lawson Daku, Latévi Max; Hagemann, Hans
Abstract: We report the DFT study of the vibrational spectroscopy properties of Mg(B3 H8 )2, a potential intermediate in the decomposition of Mg(BH4 )2, as well as those of CB11 H12 − and CB9 H10 −, whose salts can exhibit high ionic conductivities. Because the inclusion of anharmonicity is key to the accurate description of the vibrational properties of BH species [D. Sethio, L. M. Lawson Daku, H. Hagemann. Int. J. Hydrogen Energy, 41 (2016) 6814], the calculations were performed both in the harmonic and in the anharmonic approximation. The IR and Raman spectra of Cs(CB11 H12 ) and Na2 (B10 H10 ) have also been measured. The calculated and experimental spectra are in good agreement. A comparative analysis of the vibrational spectroscopy properties is made for B3 H8 − and Mg(B3 H8 )2, B12 H12 2− and CB11 H12 −, and for B10 H10 2− and CB9 H10 − . Graphical abstract: Comparison between the calculated anharmonic IR spectra of B3 H8 − and Mg(B3 H8 )2 . The BH stretching modes of B3 H8 − around 2500 cm −1 are split in Mg(B3 H8 )2 into the BHouter and BHinner stretching modes, the BHouter stretching modes being at higher frequencies than the BHinner stretching modes. The BHbridging stretching modes have even lower frequencies than the BHinner stretching modes. Highlights: Anharmonic DFT calculations were performed on Mg(B3 H8 )2, CB9 H10 − and CB11 H12 − . The effect of complexation of B3 H8 − to Mg 2+ is analyzed. New vibrational spectra for B10 H10 2− and CB11 H12 − are in good agreement with theoretical calculations.